ANALYSIS OF TRAUMATIC LEVELS OF EARTHQUAKE VICTIMS PALU, SEPTEMBER 28, 2018 - Rianti Setiadi; Franky Franky (Journal of International Conference Proceedings (JICP), 2019)
An earthquake is a disaster that causes traumatic feelings for victims such as the 7.4 SR earthquake that triggered the Tsunami in Palu, September 2018. High traumatic levels can be felt disturbing for years. People who experience trauma like this need help. Traumatic levels are thought to be influenced by gender, severe damage to their homes, family members who die, religious level, help from friends, help from the community and help from the government. If the cause of the traumatic level in the victims of the earthquake disaster can be identified, the priority of assistance can be allocated correctly. The purpose of this study is to find variables that influence the traumatic level of Palu earthquake’s victims. From the results of this study using the classification tree method it was found that the main factors that influence traumatic level are gender. Men have lower traumatic level than women. Men who get help from the government have a lower traumatic level than men who do not get help from the government. Women whose house is severely damaged have a higher traumatic level than women whose house is not severely damaged, especially for women who are less than or equal to forty years of age